Blended learning in teaching English at secondary schools in Sarawak / Magdaline Muuk - Muuk, Magdaline (2012)
The revolutions of technology and Internet have driven the development in education towards applying technology and enhancing Internet in teaching and learning. Educators are taking up the challenges to develop their teaching strategic plans. ESL teachers are having their own ways in applying the principles of teaching to digital learning environments. This paper aims to investigate teachers' why ESL teachers apply blended learning in their lesson.